Design of Supercritical Water Reactor with Thorium Fuel Cell - Rina Utami; Yanti Yulianti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
The research of desain of super critical water reactor (SCWR) thorium fuel has been done. The objective of this research is to obtain the design with high thermal power and inherent safety features. The analyzed parameters were:corefuelenrichment,reactorsize,criticality,andpowerdensitydistribution.Acorecalculationof x,y,z was achieved by CITATION code. Fuel composition and core configurations in critical condition were calculated by variation of fuel enrichment, reactor size and configuration of the fuel in the core. SCWR used thorium as fuel, stainless steel as cladding, light water as moderator and coolant as well. This research obtained critical core design that is size x = 85 cm, y = 85 cm and z = 180 cm. The critical condition can be achieved when the inner fuel loaded about 2.23% fuel enrichment and outer fuel 1.5% fuel encrichmant. The design produced 1000 MW thermal power, the maximum power density is 625.675 Watts /cc and k-effective value is 1.000274. Thereactorcoreinthisresearchfulfillstheinherentsafetystandardintermofneutronicaspect. Keywords : Core design, SCWR, thorium, power density, passive safety